Respuesta :
Solution:
Note that:
- Given expression: (-11x/2 + 3) - 2(11x/4 - 5/2)
Simplifying the expression:
- (-11x/2 + 3) - 2(11x/4 - 5/2)
- => (-11x/2 + 3) + (-11x/2 + 5)
- => -11x/2 + 3 - 11x/2 + 5
- => -22x/2 + 8
- => -11x + 8
The simplified expression is -11x + 8.
[tex] \rm \: ( - \frac{11}{2} x + 3) - 2( \frac{11}{4} x - \frac{5}{2} )[/tex]
Distribute -2 through the parentheses
[tex] \rm \: ( - \frac{11}{2} x + 3) - \frac{11}{2} x + 5[/tex]
Remove the unnecessary parentheses
[tex] \rm \: - \frac{11}{2} x + 3 - \frac{11}{2} x + 5[/tex]
Calculate the difference
[tex] \rm \: - 11x + 3 + 5[/tex]
Calculate the sum
[tex] \boxed{ \mathfrak{ - 11x + 8}}[/tex]